Al-Raysuni, Ahmad. “Sacred Text and Maṣlaḥah (Public Interest): Between Congruence and Conflict,” Year 4, Issue 13 (Summer 1419 AH/ 1998 CE), Pp. 47-65. - الريسوني أحمد (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma’rifah), 1998)
Ahmad al-Raysuni revisits the relationship between the sacred text and maṣlaḥah (public interest), and whether it is a relationship of congruency or conflict (agreement or disagreement). He calls for transcending literal approaches to fiqh texts, addressing them instead in light of real-world contexts. Al-Raysuni emphasizes that the claims of conflict between sacred text and maṣlaḥah have no basis in Islamic heritage. His study presents a historical narrative of the case, explaining the meaning of maṣlaḥah and its types (spiritual, psychological, moral, physical), and explains that the Shariʿah was revealed to bring beneficial maṣlaḥah and to ward off evil. It provides some of the rules that underpin and regulate Shariʿah maṣlaḥah-based legislation, and criticizes the claims that conflict exists between sacred text and maṣlaḥah. It then examines ways of dealing with the interpretation and application of maṣlaḥah with the sacred text, and standards of the sacred text in the assessment of maṣlaḥah.